Development of High School Students' Creative Thinking Skill Assessment Instruments on Practicum the Effect of Surface Area of Touch Field on Reaction Rates - Dini Dwi Apriyani; Nahadi Nahadi; Wiwi Siswaningsih (Universitas Sang Bumi Ruwa Jurai, 2023)
The purpose of this study was to develop an Assessment Instrument for High School Students' Creative Thinking on the Effect of Surface Area of Touch Field on Reaction Rates. The research was conducted on 15 class XI students at a high school in Bandung City and divided into 3 groups. The instruments developed were in the form of Basic Competency 4.7-based tasks and rubrics, with 8 indicators and 12 assignments, with 4 assessment rubrics per assignment. The instrument was validated by experts using a quantitative approach to validating the CVR content before being tried out. The quality of the scale is determined by the adequacy of the content using expert judgment, and an online Inter-rater Reliability test is administered and obtained by assessing students' knowledge of practical skills through the developed student worksheets. The results of this study were developed instrumentally, valid at CVR = 1, very reliable, and classified as very good with a Cronbach alpha value between 0.867 and 1.000. Based on the results of the study, it can be concluded that the performance assessment instrument developed fulfills the requirements as a good evaluation tool so it is suitable to be used as an assessment instrument to assess and measure Students' Creative Thinking Skills in practicum Effects of Surface Area of Touch Field on Reaction Rate.